On asymptotic properties of the empirical correlation matrix of a homogeneous vector-valued Gaussian field - Buldygin, V. V.; Demyanenko, O. O. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We investigate properties of the empirical correlation matrix of a centered stationary Gaussian vector field in various function spaces. We prove that, under the condition of integrability of the square of the spectral density of the field, the normalization effect takes place for a correlogram and integral functional of it.